Improving efficiency in emergency response for construction site fires: An exploratory case study - Tsai, Ming-Kuan (Journal of Civil Engineering and Management, 2016)
This study proposes an approach to assist construction managers with fire management. Since accidental fires at construction sites often go undetected until they begin to spread, they can cause serious damage. Although researchers have applied information technology to construction site safety management, few studies have focused on the relationship between information techniques and construction site fires. After investigating this relationship, the results revealed two problems: difficult fire detection and disorderly emergency response. Therefore, the intent of this study was to build an intelligent construction site fire management platform by integrating image recognition for automatic fire detection and knowledge models for immediate emergency response. Based on several tests on three common types of accidental fires at construction sites, the results demonstrated that the platform can detect fires and alert construction managers quickly. Through mobile information transmission, the construction managers were able to understand the status of on-site fires and respond appropriately. This study offers a useful reference for similar applications in construction site safety management.First published online: 27 Aug 2015